The Role of Epstein-Barr virus LMP1 Gene Expression in Oxidative Stress in Nasopharyngeal Carcinoma - Mohd Aminudin, Mustapha; Sim, Sai Peng (Japan University of Health Sciences & Japan International Cultural Exchange Foundation (JICEF), 2024)
Method: Review the article related to Epstein-Barr virus LMP1, oxidative stress and nasopharyngeal carcinoma. Results: Epstein-Barr reactivation shows overexpression of LMP1 significantly increased the level of oxidative stress. Conclusion: LMP1 expression causes cellular oxidative stress accumulation in nasopharyngeal epithelial cells, thus may be led to cancer development.